Buddhist Practice on Western Ground: Reconciling Eastern Ideals And Western Psychology. Harvey B. Aronson. - Henry, Phil (Buddhist Studies Review, 2005)
Buddhist Practice on Western Ground: Reconciling Eastern Ideals And Western Psychology. Harvey B. Aronson. Boston, MA: Shambhala Publications, 2004. xiii, 253 pp. 14.95. ISBN 1590300939.